2012
DOI: 10.1007/s10668-012-9417-x
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide handling practices by vegetable farmer in Kenya

Abstract: Pesticide handling practices have a strong bearing on the exposure of toxic effects to target and nontarget organism. A clear understanding of determinants of pesticide handling practices is a precondition in the design and implementation of policy intervention. To accomplish this, a household survey of 425 respondents was conducted in 2008. Majority of the farmers (85 %) had inappropriately handled pesticides, mainly through, unsafe storage (23 %), unsafe disposal of leftover in either sprays solutions, or ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 20 publications
(19 reference statements)
4
34
1
Order By: Relevance
“…Empirically, specific studies have shown the high human and environmental risks of unsafe use of pesticides in many African countries such as Ghana (Ntow et al 2006), Tanzania (Ngowi et al 2007), Botswana (Obopile et al 2008), Ethiopia (Jansen and Harmsen 2011), Benin (Ahouangninou et al 2012), Uganda (Kateregga 2012), Kenya (Macharia et al 2013). Other parts of sub-Saharan Africa have similar problems with the widespread use of highly toxic and illegal pesticides (Ecobichon 2001;Williamson et al 2008;Handford et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirically, specific studies have shown the high human and environmental risks of unsafe use of pesticides in many African countries such as Ghana (Ntow et al 2006), Tanzania (Ngowi et al 2007), Botswana (Obopile et al 2008), Ethiopia (Jansen and Harmsen 2011), Benin (Ahouangninou et al 2012), Uganda (Kateregga 2012), Kenya (Macharia et al 2013). Other parts of sub-Saharan Africa have similar problems with the widespread use of highly toxic and illegal pesticides (Ecobichon 2001;Williamson et al 2008;Handford et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Since Rachel Carson's Silent Spring attention has been given to the hazards of extensive pesticides use in developed and developing countries (e.g. Karlsson 2004;Hoi et al 2013;Ríos-González et al 2013;Jansen and Dubois 2014), including sub-Saharan Africa (Ngowi et al 2007;Jansen and Harmsen 2011;Stadlinger et al 2011;Kateregga 2012;Macharia et al 2013;Mengistie et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found four types of obsolete Even where legislation is sufficient information about distribution and use, enforcement is often inadequate. Like in many developing countries (Ecobichon, 2001;Kateregga, 2012;Macharia et al, 2013;Stadlinger, 2013), also Ethiopia does not have the skilled human resources nor the infrastructure to secure environmental and human health in local pesticide trade and use (PAN-UK, 2006;Williamson, 2008;Mengistie et al, 2014) and support from international parties has been too limited to make a difference (Stark, 2011;Handford et al, 2015). For instance, the WHO (2011) reported that 67% of countries in Africa knew only limited enforcement of pesticide regulations.…”
Section: Supply Chain Supporters: Signs Of Hopementioning
confidence: 99%
“…The unsafe distribution and use of pesticides in many African countries such as in Ghana (Ntow et al, 2006) Tanzania (Ngowi et al, 2007), Uganda (Kateregga, 2012), Kenya (Macharia et al, 2013) has been widely documented. Other parts of Africa have shown similar problems with poorly implemented pesticide legislation, leading to widespread use of highly toxic and illegal pesticides (Ecobichon, 2001;Williamson et al, 2008;Handford et al, 2015).…”
Section: Introductionmentioning
confidence: 99%